Mycobacterium abscessus subsp. massiliense infection secondary to traumatic anterior cruciate ligament reconstruction surgery - Emerson, Christopher P.; Brecount, Hogan; Quintero, Daniel; Greif, Dylan N.; Jose, Jean; Kaplan, Lee (Brazilian Journal of Case Reports, 2021)
Non-tuberculous Mycobacterium (NTM) infections following knee surgery are rarely reported in the literature. One month after arthroscopic lysis of adhesions from anterior cruciate ligament (ACL) reconstruction, a 67-year-old male patient presented with symptoms suggesting septic arthritis. Empiric antibiotics were initiated. Intraoperative cultures were positive for Mycobacterium abscessus. Organism-specific antimicrobial therapy with azithromycin, amikacin, and imipenem were started. Four months later the patient was switched to oral outpatient treatment with azithromycin, clofazimine and bedaquiline. Mycobacterium infections following ACL reconstruction are exceedingly rare in the United States. Successful management of Mycobacterium abscessus infection is exceptionally challenging for both orthopedists and infection disease specialists.